2019
DOI: 10.1007/s10943-019-00865-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Chaplain as a Patient Navigator and Advocate for Patients in the Intensive Care Unit: One Academic Medical Center’s Experience

Abstract: Effective communication between intensive care unit (ICU) staff, and patients and their families, can help increase understanding, trust, and goals-of-care decisions. Many strategies focus on enhancing communication by increasing family meetings or adding patient navigators. In our ICU, we implemented both strategies, uniquely appointing a chaplain for the patient navigator role. We then surveyed ICU staff on their perceptions of the chaplain/patient navigator, which yielded several valuable insights. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…17 Healthcare professionals may also perceive that healthcare chaplains provide care from the lens of a single faith , as distinct from the multi-faith service that characterises most of modern chaplaincy. 18 These misperceptions may be influenced by negative public discourse about healthcare chaplaincy as is evident in the United Kingdom and the Republic of Ireland, 16,19,20 or a perception of secularism, based on personal experiences, as distinct from the individual needs of the service user. Without a full understanding of the role, healthcare providers are likely to be hesitant to make necessary referrals.…”
Section: Introductionmentioning
confidence: 99%
“…17 Healthcare professionals may also perceive that healthcare chaplains provide care from the lens of a single faith , as distinct from the multi-faith service that characterises most of modern chaplaincy. 18 These misperceptions may be influenced by negative public discourse about healthcare chaplaincy as is evident in the United Kingdom and the Republic of Ireland, 16,19,20 or a perception of secularism, based on personal experiences, as distinct from the individual needs of the service user. Without a full understanding of the role, healthcare providers are likely to be hesitant to make necessary referrals.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients and families in the C4 Project intervention group frequently expected the chaplain PN to provide spiritual care and address medical issues and prognosis. Thus, there were anecdotal reports expressing disappointment with deferral of those questions to the ICU team ( 21 ). As a result, most ICU nurses reported that the chaplain’s background was not appropriate for the PN role ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the C4 Project, the chaplain PN was a resident enrolled in an accredited clinical pastoral education (CPE) program who had already completed one unit of CPE. As described in a prior report ( 21 ), the chaplain PN underwent special training to learn the PN role and was overseen by a CPE educator and a clinical chaplain mentor that were both very familiar with the study. The chaplain PN had few other responsibilities, except for occasional spiritual care duties outside of the project and twice weekly required CPE courses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations exist for student chaplains providing spiritual care, both in lacking experience that is increasingly needed in order to work in the complex ICU setting and in restrictions in time and balancing other responsibilities that come with their student status. 9,19 Staff chaplains appear to have greater opportunity to become integrated into the team and embedded in the activities of the MICU.…”
Section: Discussionmentioning
confidence: 99%